2022
DOI: 10.3389/fcvm.2022.770760
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neutrophil to Lymphocyte Ratio With Plaque Rupture in Acute Coronary Syndrome Patients With Only Intermediate Coronary Artery Lesions Assessed by Optical Coherence Tomography

Abstract: ObjectivesPlaque vulnerability and rupture rather than plaque size are the major cause of clinical events in patients with intermediate coronary lesions. Therefore, the present study was aimed to explore potential markers associated with plaque rupture in acute coronary syndrome (ACS) patients with intermediate coronary lesions.MethodsA total of 82 ACS patients presenting with only intermediate coronary lesions (40–70% stenosis demonstrated by quantitative coronary angiography) and no severe stenosis in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The possible mechanism of CBI caused by CEA is that NLR is related to the vulnerability of atherosclerotic plaque, that is, patients with increased NLR are more likely to have plaque rupture and microembolism. Multiple clinical studies have con rmed the correlation between NLR and atherosclerotic plaque vulnerability [23,24]. A retrospective study in China composed of 588 patients with acute ischemic stroke and 309 healthy controls free of carotid plaque showed that NLR is independent predictors of vulnerable carotid plaque in patients with acute ischemic stroke [25].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of CBI caused by CEA is that NLR is related to the vulnerability of atherosclerotic plaque, that is, patients with increased NLR are more likely to have plaque rupture and microembolism. Multiple clinical studies have con rmed the correlation between NLR and atherosclerotic plaque vulnerability [23,24]. A retrospective study in China composed of 588 patients with acute ischemic stroke and 309 healthy controls free of carotid plaque showed that NLR is independent predictors of vulnerable carotid plaque in patients with acute ischemic stroke [25].…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent publications have demonstrated a link between elevated NLR and plaque rupture in coronary artery lesions assessed by optical coherence tomography in acute coronary syndrome. 23…”
Section: Characteristics Associated With Underlying Icadmentioning
confidence: 99%
“…Lymphopenia indicates chronic inflammation and occurs secondary to the release of stress-related cortisol. An inverse relationship has been observed between lymphocyte counts and cardiac outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%